2020
DOI: 10.1017/s1047951120004333
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infections in hospitalised infants with congenital heart disease

Abstract: Objectives: To assess the overall burden and outcomes of acute respiratory infections in paediatric inpatients with congenital heart disease (CHD). Methods: This is a retrospective cross-sectional study of non-neonates <1 year with CHD in the Kid’s Inpatient Database from 2012. We compared demographics, clinical characteristics, cost, length of stay, and mortality rate for those with and without respiratory infections. We also compared those with respiratory infections who had critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…We also identified hospitalizations for respiratory illnesses among children without medical complexity. For each hospitalization, we described hospitalization-level characteristics (length of stay in days, respiratory etiology subdivided into infectious vs noninfectious [eTable 4 in Supplement 1], ICU admission, province or territory of hospitalization) and child-level characteristics (sex, age category, mortality, diagnosis code for medical technology [eg, feeding tube]). Race and ethnicity data were not available in the CIHI-DAD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified hospitalizations for respiratory illnesses among children without medical complexity. For each hospitalization, we described hospitalization-level characteristics (length of stay in days, respiratory etiology subdivided into infectious vs noninfectious [eTable 4 in Supplement 1], ICU admission, province or territory of hospitalization) and child-level characteristics (sex, age category, mortality, diagnosis code for medical technology [eg, feeding tube]). Race and ethnicity data were not available in the CIHI-DAD.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] Dramatic reductions in pediatric health care use were noted during the pandemic, due at least in part to the decrease in respiratory viral infections. [7][8][9][10][11] Children with medical complexity (CMC) are at risk of severe acute illness from respiratory infections (eg, children with cystic fibrosis, 12 congenital heart disease, 13 or sickle cell disease 14 ). In a Canadian evaluation, children who were admitted with SARS-CoV-2 infections during the early pandemic period often had existing comorbidities including obesity and neurologic impairment.…”
Section: Introductionmentioning
confidence: 99%
“…When encountering a respiratory virus, the innate immune response can be either adequate or incomplete, slowed or weakened, or delayed-in the form of an excessive response after a delay, which can lead to tissue damage [43]. This is particularly important in children with comorbidities and immunocompromised patients, including asthmatics [44,45]. In children with BA, the immune response is imbalanced and may lead to a mutually reinforcing effect of the allergic component of BA and the ARVI pathogen on the inflammation and exacerbation of respiratory tract lesions [45].…”
Section: Immune Response: Small But Important Accentsmentioning
confidence: 99%
“…In a previous study, it was explained that RTI patients underwent repeated hospitalization were known to have a history of CHD. 21 However, it stated that Klebsiella pneumonia infection increased through nosocomial transmission after cardiac surgery. 22 The results of this study found that patients with acyanotic CHD and RTI required 2 times fold longer duration These results are in line with a study conducted in Turkey, patients with subtype VSD with complications of pulmonary congestion often underwent hospitalization due to RTI even though the risk of hospitalization in the pediatric intensive care unit (ICU) is much greater.…”
Section: Comparative Study Of Hospitalization Time Of Rti Patients Be...mentioning
confidence: 99%